2016
DOI: 10.1177/2325967116675604
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Authors Differ With Regard to the Femoral and Meniscal Anatomic Parameters of the Knee Anterolateral Ligament?

Abstract: Background:No consensus exists regarding the anatomic characteristics of the knee anterolateral ligament (ALL). A critical analysis of the dissections described in previous studies allows the division of the ALL into 2 groups with similar characteristics. The presence of considerable variability suggests that the authors may not be referring to the same structure.Purpose/Hypothesis:To perform a lateral anatomic dissection, by layers, seeking to characterize the 2 variants described for the ALL on the same knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
4
40
0
2
Order By: Relevance
“…All authors agree that the ALL is attached in the lateral femoral epicondyle (Vieira et al, ; Claes et al, ; Helito et al, ; Dodds et al, ; Bonasia et al, ; Caterine et al, ; Daggett et al, ; Guenther et al, ; Kosy and Mandalia, ; Pomajzl et al, ; Roessler et al, ; Taneja et al, ; Van der Watt et al, ; Cavaignac et al, ; Helito et al, 2016a, 2016b; Macchi et al, ; Musahl et al, ; Parker and Smith, ; Runer et al, , Stijak et al, ; Roessler et al, ), but there are controversies regarding the attachment in relation to the FCL and the popliteus muscle tendon.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…All authors agree that the ALL is attached in the lateral femoral epicondyle (Vieira et al, ; Claes et al, ; Helito et al, ; Dodds et al, ; Bonasia et al, ; Caterine et al, ; Daggett et al, ; Guenther et al, ; Kosy and Mandalia, ; Pomajzl et al, ; Roessler et al, ; Taneja et al, ; Van der Watt et al, ; Cavaignac et al, ; Helito et al, 2016a, 2016b; Macchi et al, ; Musahl et al, ; Parker and Smith, ; Runer et al, , Stijak et al, ; Roessler et al, ), but there are controversies regarding the attachment in relation to the FCL and the popliteus muscle tendon.…”
Section: Discussionmentioning
confidence: 91%
“…However, there is no consensus about the association between injuries to the ALL and lateral meniscal tears. Whereas Van Dyck et al () suggested that ALL injuries are highly associated with lateral meniscal and osseus injuries, Helito et al (2016a, 2016b) found no statistical association between injuries to the ALL and the lateral meniscus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations